ERS statement on chronic thromboembolic pulmonary hypertension - Delcroix, Marion; Torbicki, Adam; Gopalan, Deepa; Sitbon, Olivier; Klok, Frederikus A.; Lang, Irene; Jenkins, David; Kim, Nick H.; Humbert, Marc; Jais, Xavier; Noordegraaf, Anton Vonk; Pepke-Zaba, Joanna; et al. (The European respiratory journal, 2021)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare complication of acute pulmonary embolism, either symptomatic or not. The occlusion of proximal pulmonary arteries by fibrotic intravascular material, in combination with a secondary microvasculopathy of vessels <500 µm, leads to increased pulmonary vascular resistance and progressive right heart failure. The mechanism responsible for the transformation of red clots into fibrotic material remnants has not yet been elucidated. In patients with pulmonary hypertension, the diagnosis is suspected when a ventilation/perfusion lung scan shows mismatched perfusion defects, and confirmed by right heart catheterisation and vascular imaging. Today, in addition to lifelong anticoagulation, treatment modalities include surgery, angioplasty and medical treatment according to the localisation and characteristics of the lesions. - This statement outlines a review of the literature and current practice concerning diagnosis and management of CTEPH. It covers the definitions, diagnosis, epidemiology, follow-up after acute pulmonary embolism, pathophysiology, treatment by pulmonary endarterectomy, balloon pulmonary angioplasty, drugs and their combination, rehabilitation and new lines of research in CTEPH. - It represents the first collaboration of the European Respiratory Society, the International CTEPH Association and the European Reference Network-Lung in the pulmonary hypertension domain. The statement summarises current knowledge, but does not make formal recommendations for clinical practice. - Tweetable abstract ERSpublications - click to tweetThe ERS statement on chronic thromboembolic pulmonary hypertension outlines a review of the literature and current practice concerning diagnosis and management of CTEPH https://bit.ly/34dIjot
Gesehen am 24.09.2021